Review of Graphene Properties in View of its Use as a Substrate for Matrix-Free Mass Spectrometry - V. A. Gabovich; V. A. Pokrovskiy (Хімія, фізика та технологія поверхні)
Short review of the graphene basic properties is given. This material is discussed, in particular, as a possible ionization support for mass spectrometry. The attention is paid to the possible role of intrinsic and deliberately induced structural defects in electronic and chemical properties of graphene substrates.